Cryptographically Sound Implementations for Typed Information-Flow Security - Fournet, Cédric; Rezk, Tamara (35th Annual ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages (POPL'08), 2008)
In language-based security, confidentiality and integrity policies conveniently specify the permitted flows of information between different parts of a program with diverse levels of trust. These policies enable a simple treatment of security, and they can often be verified by typing. However, their enforcement in concrete systems involves delicate compilation issues. We consider cryptographic enforcement mechanisms for imperative programs with untrusted components. Such programs may represent, for instance, distributed systems connected by some untrusted network. In source programs, security depends on an abstract access-control policy for reading and writing the shared memory. In their implementations, shared memory is unprotected and security depends instead on encryption and signing. We build a translation from well-typed source programs and policies to cryptographic implementations. To establish its correctness, we develop a type system for the target language. Our typing rules enforce a correct usage of cryptographic primitives against active adversaries; from an information-flow viewpoint, they capture controlled forms of robust declassification and endorsement. We show type soundness for a variant of the non-interference property, then show that our translation preserves typability. We rely on concrete primitives and hypotheses for cryptography, stated in terms of probabilistic polynomial-time algorithms and games. We model these primitives as commands in our target language. Thus, we develop a uniform language-based model of security, ranging from computational non-interference for probabilistic programs down to standard cryptographic hypotheses.